2020
DOI: 10.1098/rspb.2019.2606
|View full text |Cite
|
Sign up to set email alerts
|

Winter associations predict social and extra-pair mating patterns in a wild songbird

Abstract: Despite decades of research, our understanding of the underlying causes of within-population variation in patterns of extra-pair paternity (EPP) remains limited. Previous studies have shown that extra-pair mating decisions are linked to both individual traits and ecological factors. Here, we examine whether social associations among individuals prior to breeding also shape mating patterns, specifically the occurrence of EPP, in a small songbird, the blue tit. We test whether associations during the non-breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 59 publications
2
46
1
Order By: Relevance
“…Because persistent edges tended to be strong (Table A2), and male–female dyads with strong associations were much more likely to produce offspring, stable social affiliations appear to play an important role in reproduction in this population. While this finding supports a longstanding recognition of the importance of social pair bonds in quail life history (Calkins, 2007; Emlen & Lorenz, 1942; Gee, 2004; Leopold, 1977), it also demonstrates the utility of network approaches for capturing the patterns and timing of social behaviour relevant to reproduction in natural populations (see also Beck, Farine, & Kempenaers, 2020; Firth & Sheldon, 2016). Interestingly, genetic parentage analyses also revealed offspring from three mother–father pairs that were not strongly connected within social networks.…”
Section: Discussionsupporting
confidence: 72%
“…Because persistent edges tended to be strong (Table A2), and male–female dyads with strong associations were much more likely to produce offspring, stable social affiliations appear to play an important role in reproduction in this population. While this finding supports a longstanding recognition of the importance of social pair bonds in quail life history (Calkins, 2007; Emlen & Lorenz, 1942; Gee, 2004; Leopold, 1977), it also demonstrates the utility of network approaches for capturing the patterns and timing of social behaviour relevant to reproduction in natural populations (see also Beck, Farine, & Kempenaers, 2020; Firth & Sheldon, 2016). Interestingly, genetic parentage analyses also revealed offspring from three mother–father pairs that were not strongly connected within social networks.…”
Section: Discussionsupporting
confidence: 72%
“…Social factors operating at the individual level can generate population-level patterns in terms of which individuals are most likely to breed and with whom they reproduce. For the latter, there is increasing evidence that female–male relationships established prior to breeding can predict dyadic mating patterns (i.e., who will reproduce with whom; Rodway 2007 ; Psorakis et al 2012 ; Teitelbaum et al 2017 ; Firth et al 2018 ; Maldonado-Chaparro et al 2018 ; Beck et al 2020 ). Much less is known about whether aspects of an individual’s social position contribute toward determining its overall likelihood to breed.…”
Section: Introductionmentioning
confidence: 99%
“…During the breeding season, blue tits frequently engage in extrapair matings ( Kempenaers et al 1992 ; Delhey et al 2003 ). In winter, blue tits forage in large mixed-species flocks and female–male dyads with stronger social relationships (i.e., that spent more time foraging together) are more likely to become social or extrapair partners in the subsequent breeding season ( Beck et al 2020 ). This previous study, conducted in the same population as the present study, therefore confirmed that social associations that occurred prior to the reproductive season predicted who will breed with whom.…”
Section: Introductionmentioning
confidence: 99%
“…Female song could potentially play a role in mate choice and pair formation as females display solo song during daytime singing from winter to spring, and winter associations predict pair formation (Beck et al 2020). But importantly, the truly qualitative difference in song between sexes was the absence of female dawn song, a song display that is associated with seeking within-and extra-pair copulations by males (Kempenaers et al 1997;Parker et al 2006;Poesel et al 2004;Welling et al 1995).…”
Section: Discussionmentioning
confidence: 99%